Expression of AtWRI1 and AtDGAT1 during soybean embryo development influences oil and carbohydrate metabolism. Issue 7 (31st March 2022) - Arias, Cintia Lucía; Quach, Truyen; Huynh, Tu; Nguyen, Hanh; Moretti, Ademar; Shi, Yu; Guo, Ming; Rasoul, Amira; Van, Kyujung; McHale, Leah; Clemente, Tom Elmo; Alonso, Ana Paula; et al.
Summary: Soybean oil is one of the most consumed vegetable oils worldwide. Genetic improvement of its concentration in seeds has been historically pursued due to its direct association with its market value. Engineering attempts aiming to increase soybean seed oil presented different degrees of success that varied with the genetic design and the specific variety considered. Understanding the embryo's responses to the genetic modifications introduced, is a critical step to successful approaches. In this work, the metabolic and transcriptional responses to AtWRI1 and AtDGAT1 expression in soybean seeds were evaluated. AtWRI1 is a master regulator of fatty acid (FA) biosynthesis, and AtDGAT1 encodes an enzyme catalysing the final and rate‐limiting step of triacylglycerides biosynthesis. The events expressing these genes in the embryo did not show an increase in total FA content, but they responded with changes in the oil and carbohydrate composition. Transcriptomic studies revealed a down‐regulation of genes putatively encoding for oil body packaging proteins, and a strong induction of genes annotated as lipases and FA biosynthesis inhibitors. Novel putative AtWRI1 targets, presenting an AW‐box in the upstream region of the genes, were identified by comparison with an event that harbours only AtWRI1 . Lastly, targeted metabolomics analysis showed that carbon from sugar phosphates could be used for FA competing pathways, such as starch and cell wall polysaccharides, contributing to the restriction in oil accumulation. These results allowed the identification of key cellular processes that need to be considered to break the embryo's natural restriction to uncontrolled seed lipid increase.